Emotional Maturity Towards Career Decision-Making With Gender as a Moderator Variable Among Students - Hanafi, Rosyid (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Career decisions are a process in which a person selects from several options in planning their future, therefore students must have good emotional maturity. The purpose of this research is to determine the relationship between emotional maturity and career decision-making. This research uses quantitative research with a correlational method. The measurement tool used in the emotional maturity scale was developed based on the aspects proposed by Walgito (2004) and the career decision scale proposed by Pearson. (2004). The sample size in this study consisted of 115 students from the NWDI Ajan vocational school. The data collection method used purposive sampling scale. The research results indicate a significant influence of emotional maturity on career decision-making among students, evidenced by a Pearson correlation value of 0.133 with a significance (2-tailed) of (0.200), meaning 0.200 > 0.05. These research findings show a significant positive correlation between emotional maturity and students' career planning. Keywords: Emotional Maturity, Career Decision Making, Gender